Analyses of haplotypes of TLR2 and TLR3 genes for COVID-19 prognosis in a cohort of professionals who worked in the first pandemic wave in Belém-PA, Brazil - Silva, Marcos Jessé Abrahão; Figueira, Luiza Raquel Tapajós; Sardinha, Daniele Melo; Costa da Cruz, Eliete; Andrade, Natasha Cristina Oliveira; Bispo, Sebastião Kauã De Sousa; Augusto Ferreira Dos Anjos, Thiago; Dos Santos, Everaldina Cordeiro; Garcia, Ana Judith Pires; Lima, Luana Nepomuceno Gondim Costa (Frontiers in Genetics, 2025)
Coronavirus disease 2019 (COVID-19) is a multisystemic disease caused by SARS-CoV-2 that can lead to several pulmonary illnesses according to the immunological contexts of the individual. Haplotypes consist of single-nucleotide polymorphisms (SNPs) within candidate genes for diseases. TLR2 and TLR3 are genes located on human chromosome 4 (chr:4) and composite a haplotype that influence immune signaling and inflammatory pathways. The purpose of this article was to genetically analyze in silico a cohort of professionals from Belém-PA during the first wave of the pandemic using SNPs rs3804100, rs3775290, and rs3775291 on the human chr:4. This is a computational genomic design using bioinformatic software and machine-learning technologies on epidemiological data of Sanger sequencing data. Regarding the findings, none of the alleles formed by the haplotype showed statistical significance for symptomatology or disease severity. The haplotype block was not significant between the SNPs analyzed despite a high permutation rate of alleles at the beginning of the variance of the individual genomic data. Then, the TLR2–TLR3 haplotype (SNPs rs3804100, rs3775290, and rs3775291) showed little determination in the clinic of individuals with COVID-19 in Belém (Northern Brazil), which may indicate differences in collective genetic patterns and/or epigenetic influences compared to other more affected populations that have the same haplotype pattern.